Pengaruh Kompensasi dan Komunikasi Internal Terhadap Kinerja Dosen Tetap di Universitas Muhammadiyah Plembang - Fatnawaty, Tri Fatrie (Universitas muhammadiyah palembang, 2011)
This researchexamines 1) Compensation partial effect on peformance perment lecturer Universitas Muhammadiyah Palembang 2) interpersonal communication partial effect on the peformance permanent lecturer University of Muhammadiyah Palembang . The population in this study are 96 people lecturer University of Muhammadiyah Palembang. From the result of calculations shows taht:1) The value of regression coefficient compensation (X1) amounted to 0,546. meaning compensation effect the peformance of lecturer (Y) equal to 0,622, mean interpersonal communication effect the performance of lecture (Y) equal to 0,662 and 3)Based on the F test is know that there is there is influence compensation (X1) and interpersonal communication (X2) on the performeace lecture (Y) implementation is the research can add new paradigm for decision makers at the University of Muhammadiyah Palembang in an effort to boost the performance of lecturer of through improved compensation an interpersonal communication